2019
DOI: 10.1158/1078-0432.ccr-18-1984
|View full text |Cite
|
Sign up to set email alerts
|

Intertumoral Heterogeneity of CD3+ and CD8+ T-Cell Densities in the Microenvironment of DNA Mismatch-Repair–Deficient Colon Cancers: Implications for Prognosis

Abstract: Background: Colorectal cancers with deficient DNA mismatch repair (dMMR) are presumed to uniformly have dense lymphocytic infiltration that underlies their favorable prognosis and is critical to their responsiveness to immunotherapy, as compared to MMR-proficient (pMMR) tumors. We examined T-cell densities and their potential heterogeneity in a large cohort of dMMR tumors. Experimental Design: CD3+ and CD8+ T-cell densities were quantified at the invasive margin (IM) and tumor core (CT) in 561 stage III colo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 41 publications
5
62
1
Order By: Relevance
“…As noted, there were several studies for the densities of stromal TILs at the invasive margin in colorectal cancer. The density of each subset of T cells is significantly differed according to location, and lower densities of CD3+ and CD8+ T cells at invasive margin was associated with shorter OS [33,34]. Unlike in colorectal cancer, the number of poorly cohesive carcinomas is high in stomach cancer.…”
Section: Discussionmentioning
confidence: 97%
“…As noted, there were several studies for the densities of stromal TILs at the invasive margin in colorectal cancer. The density of each subset of T cells is significantly differed according to location, and lower densities of CD3+ and CD8+ T cells at invasive margin was associated with shorter OS [33,34]. Unlike in colorectal cancer, the number of poorly cohesive carcinomas is high in stomach cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Our finding that low TIL densities were significantly and independently associated with poorer DFS in the overall cohort is consistent with previous studies of TILs in CRC, including a population-based cohort, 18 case series of pooled tumor stages and variable treatment, 4 and data for CD3 þ and CD8 þ T cell densities and Immuno-score®. 4,5 We made the novel observation that TIL densities Figure 3. Relative contribution (percent) of (A) tumor-infiltrating lymphocytes (TILs), (B) tumor budding, and (C) the budding/TILs combined variable to diseasefree survival (DFS) in the overall cohort of patients with stage III colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of our study include the large number of samestage patients with uniform treatment in a clinical trial and with long-term follow-up. In addition to TILs, intratumoral CD3 þ and CD8 þ T-cells 5 or the Immunoscore® (which uses a complex proprietary algorithm 4 ) has been shown to provide prognostic information in patients with colon cancer. However, analysis of TILs, as shown here, can be performed in routine histological tumor sections with concurrent determination of tumor budding.…”
Section: Annals Of Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning stage III CRC, contrasting data are available in the literature. While Laghi et al showed that CD3 infiltrates cannot be independently used to predict patient clinical outcomes,17 Sinicrope and Pagès, in two different clinical trials addressing FOLFOX-based adjuvant chemotherapy, demonstrated that CD3+ densities can independently predict patient outcomes in stage III CC 18 19…”
Section: Introductionmentioning
confidence: 99%